Study on a 110 kV combined prefabricated joint fault caused by premature failure of grounding grid. (November 2022) - Huang, Jiasheng; Ye, Zhechi; Zhang, Gengbin; Bao, Shuzhen; Wang, Pengyu; Liu, Gang
Highlights: The impact of premature failure of the grounding grid is studied. Based on the smoothness of the epoxy insulator, the breakdown process is phased. 2D cable joint models are built to describe the actual breakdown process. The discharge-damage mechanism of joint insulation is proposed. Abstract: The grounding grid on the outside of the epoxy insulator breaks under the long-term oxidative corrosion of moisture, fails prematurely, and may eventually develop into a breakdown failure. However, the impact of this process has not yet been discovered. In this paper, a 110 kV combined prefabricated cable joint breakdown fault is discussed. Through the inspection and comparative analysis of the faulty joint, it is speculated that the premature failure of the grounding grid causes the breakdown of the epoxy insulator. The fault process can be divided into the grounding failure stage and the insulation damage stage. In this paper, the corresponding two-dimensional electric field simulation calculation model is established, the fault development process is restored, and the possible effects of different stages is analyzed. The results show that due to the corrosive effect of moisture, when the grounding grid is broken, a floating potential will be generated on the surface of the epoxy insulator. With the expansion of the grounding failure range, the local field strength on the surface of the epoxy insulator is distorted, which will cause partial discharge. When the failure range is 220 mm, the electric field distortion of the joint reaches the maximum value of 23.3MV/m, which will destroy the insulation strength of the epoxy insulator and cause insulation breakdown, eventually leading to an accident. The research results point out the importance of the continuity of the grounding grid, and the improvement measure is proposed to reduce the occurrence of such accidents. The analysis method for cable joint failure case can provide a reference for dealing with similar accidents.